Strengthening The Social Capital of The Banda Neira Community to Improve The Adaptive Capacity of Tsunami Mitigation - Triyono Triyono; Dyan Primana Sobarudin; Ana Rojayati; Muhammad Hikmat Jayawiguna (Jurnal Segara, 2022)
Adaptive capacity is one of the essential components of tsunami disaster mitigation. One of the determinants of the high level of adaptive capacity is the strength of the community’s social capital. Social capital plays an essential role as the basis for community response, especially during the emergency period. Communities with good social capital positively affect the implementation of tsunami mitigation strategies. This study seeks to assess the actual condition of the adaptive capacity of the Banda Neira community in dealing with the tsunami disaster and efforts to increase it through strengthening social capital. The adaptive capacity assessment uses an index-based approach by identifying a set of determinants based on respondent interviews related to perceptions and knowledge of disaster mitigation. The three variables of social capital (bonding, bridging, and linking) are used to measure each determinant numerically or qualitatively with the value of the Likert model scale (1-5). Furthermore, the determinant scores are combined into a measurement of the overall adaptive capacity of the system. The results of the research indicate that it is necessary to strengthen the bounding and bridging variables, namely in the form of increasing the role and function of institutions in assisting, preparedness training, and strengthening relations between communities through social activities and optimizing the role of social groups.